Surface functionalization of Ti6Al4V with an extract of polyphenols from red grape pomace. (August 2021) - Riccucci, G.; Cazzola, M.; Ferraris, S.; Gobbo, V.A.; Guaita, M.; Spriano, S.
Graphical abstract: Highlights: Chemically treated Ti6Al4V can be surface functionalized with polyphenols from red grape pomace. The grafting link is between deprotonated OH surface groups and Ca2+ ions forming a complex with the polyphenols. The grafted polyphenols have redox chemical and radical scavenging ability on the metallic surface. The polyphenols are released in aqueous media. The functionalized surfaces can be sterilized by gamma irradiation. Abstract: The focus of the paper is on effectiveness of a functionalization process with natural polyphenols on a chemically treated and bioactive Ti6Al4V alloy, on the grafting mechanism, and the redox/scavenging activity of the grafted biomolecules. Polyphenols (phenolic acids, flavonoids, and condensed tannins) are extracted from organic red grape pomace. The functionalization process is performed at pH = 7.4 with the addition of calcium ions, which act as a bridge between the substrate and polyphenols. The presence, amount (semi-quantitative), distribution, release, and type of bonding to the surface of the grafted polyphenols have been assessed. The functionalized samples have a homogeneous distribution of polyphenols as a continuous layer and micro-sized agglomerates. The grafted polyphenols maintain redox chemical and radical scavenging ability. A fraction of polyphenols is released into water in one day, while a firmly grafted layer remains on the surface even after four weeks. A complete release can occur in case of an environment with pH of 4–5 (e.g. inflammation). The functionalized surfaces can be sterilized by gamma irradiation without significant damage of the grafted polyphenols.